Bangladesh : Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper reviews Bangladesh's Interim Poverty Reduction Strategy Paper (I-PRSP). The paper addresses the question as to 'what are the broad lessons from the past development experience.' It captures the salient features of social progress notwithstanding the challenging odds facing the country. The paper reviews the trends of poverty to set the benchmark for the subsequent discussion on poverty targets as well as antipoverty policy and institutional actions necessary to achieve the targets. The paper also sets the major targets and goal posts sketching a transition path for Bangladesh.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet